Music and refugees' wellbeing in contexts of protracted displacement. (February 2019) - Millar, Oscar; Warwick, Ian
Objectives: The aim of this study was to improve understanding of the relationship between music practice and the wellbeing of young refugees, by examining the perspectives of Yazidi music participants aged 11–18. Design: Focused exploratory case study design, informed by the Ottawa Charter for Health Promotion which provided the conceptual framework for the research. Setting: A camp in northern Greece, where people from Iraq and Syria had been living for up to a year. Method: Data were collected over a 5-week period through participant observation of individual music lessons and group music workshops involving between 3–12 participants. In addition, semi-structured interviews were conducted with a sub-sample of six participants (three boys and three girls) aged 11–18. Results: Findings indicate that activities involving music practice can impact positively on young people's wellbeing, enabling the development of emotional expression, improved social relations, self-knowledge and positive self-identification, and a sense of agency. Conclusion: The positive impacts of music practice noted here suggest it has the potential to be a promising health promotion approach for young refugees, by helping to develop supportive environments, through which community action can be strengthened and personal skills developed.